Impact of male-female cohabitation period on behavioral aspects, fertility, hatchability, and hormonal estimates of Japanese quail - Ahmed Abdel-Kareem Abuoghaba (Elsevier, 2022)
ABSTRACT: To evaluate the impact of male-female cohabitation period on the fertility, hatchability, injuries response, and some hormonal estimates in Japanese quails. A total of 288 mature Japanese quails were equally divided into 3 groups (3 groups × 8 replicates × 12 birds), with 1 Male: 2 Females sex ratio. In the first group (control), male and female quails were reared continuously together, while the males in the second and third groups were reared together with females once or twice/wk times (24 h/ time), respectively throughout the experiment. The obtained results showed that final body weight (FBW/g), fertility (%), and hatchability (%) in the second and third groups significantly (P ≤ 0.01) increased compared with the control group. Laying quails in the second and third groups significantly (P ≤ 0.01) produced more and heavier eggs, while the feed consumption and feed conversion ratio were significantly (P ≤ 0.01) decreased compared with the control group. The injuries response for both sex in the second and third groups significantly (P ≤ 0.01) decreased compared with the control group. The cloacal size (mm2) for quails in the third group significantly (P ≤ 0.01) increased than those of the first and second groups, while the testes (%) were not affected. The testosterone hormone concentration for male chickens in the second and third groups significantly (P < 0.01) decreased, while the female progesterone hormone concentration (ng/mL) significantly (P < 0.01) increased compared with the control group. The means of red blood cells (RBC/106), white blood cells (WBC/103), and hemoglobin (g/dL) for quails in the second and third groups significantly (P < 0.01) increased, while heterophil/lymphocyte (H/L ratio) significantly (P < 0.01) decreased compared with the control group. Thus, it could be concluded that the reduction male-female cohabitation period of quails is recommended for improving the fertility and hatchability percentages as well as and some hormonal estimates.